Synaptotagmin XIII expression and peritoneal metastasis in gastric cancer. Issue 10 (9th May 2018) - Kanda, M.; Shimizu, D.; Tanaka, H.; Tanaka, C.; Kobayashi, D.; Hayashi, M.; Takami, H.; Niwa, Y.; Yamada, S.; Fujii, T.; Sugimoto, H.; Kodera, Y.
Abstract : Background: Peritoneal metastasis is a frequent cause of death in patients with gastric cancer. The aim of this study was to identify molecules responsible for mediating peritoneal metastasis of gastric cancer. Methods: Transcriptome and bioinformatics analyses were conducted to identify molecules associated with peritoneal metastasis. The therapeutic effects of intraperitoneally administered small interfering (si) RNA were evaluated using mouse xenograft models. Expression of mRNA and protein was determined in gastric tissues from patients with gastric cancer. Results: Synaptotagmin XIII ( SYT13 ) was expressed at significantly higher levels in patients with peritoneal recurrence, but not in those with hepatic or distant lymph node recurrence. Inhibition of SYT13 expression in a gastric cancer cell line transfected with SYT13‐ specific siRNA (si SYT13 ) was associated with decreased invasion and migration ability of the cells, but not with proliferation and apoptosis. Intraperitoneal administration of si SYT13 significantly inhibited the growth of peritoneal nodules and prolonged survival in mice. In an analysis of 200 patients with gastric cancer, SYT13 expression in primary gastric cancer tissues was significantly greater in patients with peritoneal recurrence or metastasis. A high level of SYT13 expression in primary gastric cancer tissues was an independent risk factor for peritoneal recurrence. Conclusion: SYT13 expression in gastric cancer is associated with perioneal metatases and is a potential target for treatment. Abstract : Potential target for therapy